Coronary surgery in elderly: it is never too late - Chivasso, Pierpaolo; Benedetto, Umberto (Journal of Thoracic Disease, 2016)
The optimal revascularization strategy for patients with multivessel coronary artery disease (CAD) remains still debated (1-3). The decision to recommend coronary artery bypass grafting (CABG) or percutaneous coronary intervention (PCI) should be driven by a comparison of the short-term and long-term effect on outcomes. It seems to be a large body of evidence from randomized controlled trials supporting a survival advantage from CABG compared with PCI in patients with multivessel CAD, in keeping with previous findings from large observational studies (4-7). These results have been similarly demonstrated both in the era of balloon angioplasty and bare metal stents (BMS) and in the era of drug-eluting stents (DES).